THE TABLET FORMULATIONS EFERVESEN EXTRACT OF CINNAMON BARK WITH VARIATIONS IN THE TYPE OF SWEETENER - Andini, Septia; Rustiani, Erni; Indriati, Dwi (Universitas Pakuan, 2018)
Cinnamon Bark contains flavonoids, tannins, alkaloids, and phenols. Phenolic compounds contained in cinnamon is a sinamat acid is effective as anti diabetic. This research aims to determine the formula preparations tablets efervesen extract of cinnamon bark with a certain type of sweetener that favored the panelists and the levels of sinamat acid in efervesen tablets and extracts. The formula is made with different types of sweeteners such as aspartame stevia 1.5%, 3.5% and 1% sukralosa. The results of the analysis showed no difference in sweeteners influence against the parameters of color and scent but the effect on the parameters of taste every formula. Formula tablets efervesen extract of cinnamon bark that is favored by panelists based on based on the parameters of taste is formula 1 with the sweetener aspartame concentration of 1.5% and a formula 3 with sweetener sukralosa concentration 1% preferred formula panelists. The results of the analysis of the levels of sinamat acid in extract of cinnamon bark obtained the level of 471, 13 mg/g as for Formula 1 tablet efervesen acquired the levels of 369.76 mg/gram